Association between corticosteroid use and 28-day mortality in septic shock patients with gram-negative bacterial infection: a retrospective study - Dong, Yi; Heng, Gang; Zhang, Jianxin; Shen, Yanbing; Lan, Zhen; Wei, Kunchen; Jin, Weidong (Frontiers in Medicine, 2023)
Purpose: Corticosteroids are recommended in the 2021 Surviving Sepsis Campaign (SSC) guidelines, while the effects on short-term mortality remain conflicting. We initiated our study to identify whether corticosteroids altered 28-day mortality in septic shock patients with gram-negative bacterial infection.A total of 621 patients with septic shock and gram-negative bacteria culture results were identified from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. Propensity score matching (PSM) was performed and Kaplan-Meier survival curve analyses with log-rank tests were used to determine the association between corticosteroids use and the risk of 28-day mortality. Subgroup analyses were used to estimate whether the conclusion is stable and reliable.Results: Corticosteroid administration was associated with increased 28-day mortality in septic shock patients with gram-negative bacterial infection (log-rank test P =0.028).Patients who received corticosteroids obtained a higher incidence of stage 2-3 AKI and higher hospital mortality. The incidence of stage 2-3 AKI in early period significantly mediated the relationship between corticosteroids use and 28-day mortality (P =0.046 for the average causal mediation effect (ACME)). Interaction tests indicated the effect of corticosteroids use was maintained in patients with neutrophils to lymphocytes ratio (NLR) of <20 (P for interaction =0.027).Conclusions: Systemic corticosteroids use could be harmful in septic shock patients with gram-negative bacterial infection, especially in patients with relatively low NLR.